Pengaruh Beban Kerja Perawat terhadap Penerapan Patient Safety dengan Organizational Citizenship Behavior (OCB) sebagai Variabel Mediator di Rumah Sakit Jannah Kota Serang - Tika Novriyanti; Arlette Suzy Puspa Pertiwi; Rizki Adriansyah Rubini (IAI Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of physical and mental workload on the implementation of patient safety at Jannah Hospital, Serang City, with Organizational Citizenship Behavior (OCB) as a mediator variable. The research method used was quantitative with a cross-sectional design. Data were collected through questionnaires distributed to 89 respondents using a simple random sampling technique. Data analysis was performed using the Chi-square test and path analysis using SmartPLS software. The results showed that physical workload had a negative and significant effect on the implementation of patient safety (p = 0.002; coefficient -0.247). Conversely, mental workload did not show a significant effect on patient safety (p = 0.146; coefficient -0.135). Simultaneously, physical and mental workload influenced patient safety with an R-square value of 0.343. Furthermore, OCB was shown to significantly mediate the relationship between physical workload and patient safety (p = 0.047; coefficient –0.106), but OCB's mediation of the relationship between mental workload and patient safety was not significant (p = 0.280; coefficient –0.079). Based on these findings, the study recommends managing physical and mental workload through stress management programs, establishing a more balanced work schedule, and improving communication and collaboration between nurses. Furthermore, it is important to strengthen a work culture that supports OCB and rewards extra-role behavior. Further research with a larger sample size and additional variables such as organizational support and job satisfaction is recommended to gain a more comprehensive understanding of the influence of workload on patient safety.